DETERMINAN WORD-OF-MOUTH COMMUNICATION STUDI PADA KONSUMEN KERETA API PURWOJAYA KORIDOR PURWOKERTO-JAKARTA - Astogini, Dwiwiyati (Faculty of Economics and Business Universitas Jenderal Soedirman, 2010)
The aim of this research is to measure the affect of customer satisfaction to word of mouth, confirmatory factor analyses used in this research. By using 110 sample with purposive sampling. The result of this research there are positive affect train tangibles, station tangibles, personel, reliability, empathy, image to customer satisfaction. Customer satisfaction affected to Word Of Mouth.